Educological Principles of Training Experts for the Education System of Ukraine: Achievements and Prospects - Olena Protsenko; Viktor Ogneviuk; Svitlana Sysoieva; Olha Melnychenko (Jesuit University Ignatianum in Krakow, 2021)
RESEARCH OBJECTIVE: The problem of introducing expert examination of education management is relevant and pressing for Ukraine in the context of assessment of education quality at all levels. The purpose of the article is to substantiate the effectiveness of the model of training experts in the field of education on the basis of educology at Borys Grinchenko Kyiv University. THE RESEARCH PROBLEM AND METHODS: When processing the obtained empirical data, statistical methods were used to compare the indicators of the Master's student survey before and after the course of educology according to Pearson's criteria, Fisher's test, and the Mann-Whitney-U test Venn diagram. THE PROCESS OF ARGUMENTATION: Training experts in the field of education is based on the model: 1) mastering the basics of educology and its components; 2) mastering the methodology of the examination and the ethical standards of its implementation; and 3) mastering the specifics of the educational segment which is subject to expert examination. RESEARCH RESULTS: The study confirms the efficiency of the developed model of experts' training in the field of education. Educology provides the system, purposefulness and effectiveness for such training. CONCLUSIONS, INNOVATIONS, AND RECOMMENDATIONS: The results of the study provide an opportunity to see the feasibility of the first level of the model, which involves mastering the basics of educology; the second level, which is aimed at mastering the components of the educational program, which reveal the methodology and specifics of expert activities; and the third level, which makes it possible to differentiate the suggested directions of such training, namely: measuring and monitoring the quality of education, education management, educational economics, and educational law